2019
DOI: 10.15649/cuidarte.v10i2.641
|View full text |Cite
|
Sign up to set email alerts
|

Estudiantes universitarios y su incursión en el alcohol, tabaco y otras sustancias

Abstract: Introducción: El presente estudio tuvo como objetivo identificar la cantidad de estudiantes en una institución de educación superior en el interior paulista que experimentan su incursión en el alcohol, el tabaco y otras sustancias, y evaluar así la ocurrencia y el nivel de dependencia de los mismos. Materiales y Métodos: Se trata de un extracto de un estudio de levantamiento, exploratorio, descriptivo, de enfoque cuantitativo, realizado con 416 estudiantes universitarios. Los datos fueron recolectados en el tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…Por fim, no sexto artigo, Gonçalves et al, (2019) O envolvimento em atividades extracurriculares é destacado como um meio de desenvolver habilidades sociais, construir relacionamentos saudáveis e ocupar o tempo de maneira produtiva, reduzindo assim a probabilidade de envolvimento com drogas (SILVA et al, 2019).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Por fim, no sexto artigo, Gonçalves et al, (2019) O envolvimento em atividades extracurriculares é destacado como um meio de desenvolver habilidades sociais, construir relacionamentos saudáveis e ocupar o tempo de maneira produtiva, reduzindo assim a probabilidade de envolvimento com drogas (SILVA et al, 2019).…”
Section: Resultsunclassified
“…Desse modo, os fatores de prevenção enfatizados incluem educação e conscientização, ambiente familiar saudável, envolvimento em atividades extracurriculares, desenvolvimento de habilidades de enfrentamento e apoio social. Os programas de prevenção também são citados como um meio de empoderar os adolescentes para tomar decisões informadas e construir relacionamentos saudáveis (SILVA, 2019;SILVA et al, 2019).…”
Section: Resultsunclassified
“…Regarding sex, despite having lost association in the adjusted model, several studies have pointed to an association with abusive consumption of alcoholic beverages (Grucza et al, 2018; Jao et al, 2019; Malta et al, 2021; Rodríguez-Muñoz et al, 2020; Silva et al, 2019), mainly, the increase in consumption by women (Grucza et al, 2018; Rodríguez-Muñoz et al, 2020) which raises some concern, as women seem to be more vulnerable to damage caused by alcohol (Gomes et al, 2018). Although we had a higher proportion of female university students in our study, and there was no association in the adjusted model, we found an indication in the univariate analysis of females to be a protective factor for abusive consumption of alcoholic beverages, different from the trend observed in other studies.…”
Section: Discussionmentioning
confidence: 99%